mirror of
https://github.com/kalmarek/GroupRings.jl.git
synced 2024-12-28 02:40:28 +01:00
Merge remote-tracking branch 'origin/AutFn' into enh/julia-v0.7
This commit is contained in:
commit
ecc44a8da6
@ -340,8 +340,43 @@ function -(X::GroupRingElem{S}, Y::GroupRingElem{T}) where {S, T}
|
||||
addeq!((-Y), X)
|
||||
end
|
||||
|
||||
@doc doc"""
|
||||
mul!(result::AbstractArray{T},
|
||||
doc"""
|
||||
fmac!(result::AbstractVector{T},
|
||||
X::AbstractVector,
|
||||
Y::AbstractVector,
|
||||
pm::Array{Int,2}) where {T<:Number}
|
||||
> Fused multiply-add for group ring coeffs using multiplication table `pm`.
|
||||
> The result of X*Y in GroupRing is added in-place to `result`.
|
||||
> Notes:
|
||||
> * this method will silently produce false results if `X[k]` is non-zero for
|
||||
> `k > size(pm,1)`.
|
||||
> * This method will fail if any zeros (i.e. uninitialised entries) are present
|
||||
> in `pm`.
|
||||
> Use with extreme care!
|
||||
"""
|
||||
|
||||
function fmac!(result::AbstractVector{T},
|
||||
X::AbstractVector,
|
||||
Y::AbstractVector,
|
||||
pm::Array{Int,2}) where {T<:Number}
|
||||
z = zero(T)
|
||||
s1 = size(pm,1)
|
||||
s2 = size(pm,2)
|
||||
|
||||
@inbounds for j in 1:s2
|
||||
if Y[j] != z
|
||||
for i in 1:s1
|
||||
if X[i] != z
|
||||
result[pm[i,j]] += X[i]*Y[j]
|
||||
end
|
||||
end
|
||||
end
|
||||
end
|
||||
return result
|
||||
end
|
||||
|
||||
doc"""
|
||||
mul!(result::AbstractVector{T},
|
||||
X::AbstractVector,
|
||||
Y::AbstractVector,
|
||||
pm::Array{Int,2}) where {T<:Number}
|
||||
@ -360,24 +395,12 @@ function mul!(result::AbstractVector{T},
|
||||
pm::Array{Int,2}) where {T<:Number}
|
||||
z = zero(T)
|
||||
result .= z
|
||||
lY = length(Y)
|
||||
s = size(pm,1)
|
||||
|
||||
@inbounds for j in 1:lY
|
||||
if Y[j] != z
|
||||
for i in 1:s
|
||||
if X[i] != z
|
||||
pm[i,j] == 0 && throw(ArgumentError("The product don't seem to be supported on basis!"))
|
||||
result[pm[i,j]] += X[i]*Y[j]
|
||||
end
|
||||
end
|
||||
end
|
||||
end
|
||||
return result
|
||||
return fmac!(result, X, Y, pm)
|
||||
end
|
||||
|
||||
@doc doc"""
|
||||
mul!(result::GroupRingElem{T},
|
||||
doc"""
|
||||
mul!{T}(result::GroupRingElem{T},
|
||||
X::GroupRingElem,
|
||||
Y::GroupRingElem)
|
||||
> In-place multiplication for `GroupRingElem`s `X` and `Y`.
|
||||
|
@ -211,4 +211,92 @@ using SparseArrays
|
||||
end
|
||||
|
||||
end
|
||||
|
||||
@testset "SumOfSquares in group rings" begin
|
||||
∗ = star
|
||||
|
||||
G = FreeGroup(["g", "h", "k", "l"])
|
||||
S = G.(G.gens)
|
||||
S = [S; inv.(S)]
|
||||
|
||||
ID = G()
|
||||
RADIUS=3
|
||||
@time E_R, sizes = Groups.generate_balls(S, ID, radius=2*RADIUS);
|
||||
@test sizes == [9, 65, 457, 3201, 22409, 156865]
|
||||
E_rdict = GroupRings.reverse_dict(E_R)
|
||||
pm = GroupRings.create_pm(E_R, E_rdict, sizes[RADIUS]; twisted=true);
|
||||
RG = GroupRing(G, E_R, E_rdict, pm)
|
||||
|
||||
g = RG.basis[2]
|
||||
h = RG.basis[3]
|
||||
k = RG.basis[4]
|
||||
l = RG.basis[5]
|
||||
G = (1-RG(g))
|
||||
@test G^2 == 2 - RG(g) - ∗(RG(g))
|
||||
|
||||
G = (1-RG(g))
|
||||
H = (1-RG(h))
|
||||
K = (1-RG(k))
|
||||
L = (1-RG(l))
|
||||
GH = (1-RG(g*h))
|
||||
KL = (1-RG(k*l))
|
||||
|
||||
X = (2 - ∗(RG(g)) - RG(h))
|
||||
Y = (2 - ∗(RG(g*h)) - RG(k))
|
||||
|
||||
@test -(2 - RG(g*h) - ∗(RG(g*h))) + 2G^2 + 2H^2 == X^2
|
||||
@test (2 - RG(g*h) - ∗(RG(g*h))) == GH^2
|
||||
@test -(2 - RG(g*h*k) - ∗(RG(g*h*k))) + 2GH^2 + 2K^2 == Y^2
|
||||
@test -(2 - RG(g*h*k) - ∗(RG(g*h*k))) +
|
||||
2(GH^2 - 2G^2 - 2H^2) +
|
||||
4G^2 + 4H^2 + 2K^2 ==
|
||||
Y^2
|
||||
|
||||
@test GH^2 - 2G^2 - 2H^2 == - X^2
|
||||
@test -(2 - RG(g*h*k) - ∗(RG(g*h*k))) + 4G^2 + 4H^2 + 2K^2 == 2X^2 + Y^2
|
||||
|
||||
@test GH^2 == 2G^2 + 2H^2 - (2 - ∗(RG(g)) - RG(h))^2
|
||||
@test KL^2 == 2K^2 + 2L^2 - (2 - ∗(RG(k)) - RG(l))^2
|
||||
|
||||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) + 2*GH^2 + 2*KL^2 ==
|
||||
(2 - ∗(RG(g*h)) - RG(k*l))^2
|
||||
|
||||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) +
|
||||
2(2G^2 + 2H^2 - (2 - ∗(RG(g)) - RG(h))^2) +
|
||||
2(2K^2 + 2L^2 - (2 - ∗(RG(k)) - RG(l))^2) ==
|
||||
(2 - ∗(RG(g*h)) - RG(k*l))^2
|
||||
|
||||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) +
|
||||
2(2G^2 + 2H^2) +
|
||||
2(2K^2 + 2L^2) ==
|
||||
(2 - ∗(RG(g*h)) - RG(k*l))^2 +
|
||||
2(2 - ∗(RG(g)) - RG(h))^2 +
|
||||
2(2 - ∗(RG(k)) - RG(l))^2
|
||||
|
||||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) +
|
||||
2(2 - ∗(RG(g*h*k)) - RG(g*h*k)) + 2L^2 ==
|
||||
(2 - ∗(RG(g*h*k)) - RG(l))^2
|
||||
|
||||
@test 2 - ∗(RG(g*h*k)) - RG(g*h*k) ==
|
||||
2GH^2 + 2K^2 - (2 - ∗(RG(g*h)) - RG(k))^2
|
||||
|
||||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) +
|
||||
2(2GH^2 + 2K^2 - (2 - ∗(RG(g*h)) - RG(k))^2) + 2L^2 ==
|
||||
(2 - ∗(RG(g*h*k)) - RG(l))^2
|
||||
|
||||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) +
|
||||
2(2GH^2 + 2K^2) + 2L^2 ==
|
||||
(2 - ∗(RG(g*h*k)) - RG(l))^2 +
|
||||
2(2 - ∗(RG(g*h)) - RG(k))^2
|
||||
|
||||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) +
|
||||
8G^2 + 8H^2 + 4K^2 + 2L^2 ==
|
||||
(2 - ∗(RG(g*h*k)) - RG(l))^2 + 2(2 - ∗(RG(g*h)) - RG(k))^2 + 4(2 - ∗(RG(g)) - RG(h))^2
|
||||
|
||||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) +
|
||||
2GH^2 + 2KL^2 == (2 - ∗(RG(g*h)) - RG(k*l))^2
|
||||
|
||||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) + 2(2G^2 + 2H^2) + 2(2K^2 + 2L^2) ==
|
||||
(2 - ∗(RG(g*h)) - RG(k*l))^2 + 2(2 - ∗(RG(k)) - RG(l))^2 + 2(2 - ∗(RG(g)) - RG(h))^2
|
||||
end
|
||||
end
|
||||
|
Loading…
Reference in New Issue
Block a user